Mapping the Soil Frontiers with Legacy Soil Data: An Approach for Covering the Lack of Updated Reference Maps of Minas Gerais, Brazil - Vasconcelos, Bruno Nery Fernandes; Bravo, João Vitor Meza; Cunha, Jorge Eduardo Ferreira; Fernandes-Filho, Elpídio Inácio (Anuário do Instituto de Geociências, 2023)
Digital Soil Mapping (DSM) of large areas is a time-consuming and expensive process, where soil scientists take as many as possible observations to predict soil classes and their attributes. Sometimes, the DSM is made in geographic regions with no updated geographic information, leading the soil scientist to depend on Legacy Soil Data (LSD). However, LSD is not always available at an adequate scale or resolution, forcing soil scientists to find creative solutions. Here we present a method for mapping soil frontiers with no updated reference data. We demonstrate that by combining different LSD sources with adequate predictive environmental covariables, the results could be consistent enough for mapping the soil frontiers of a large geographic region without updated reference data. For doing that, we have adopted the full geographic extension of Minas Gerais state – Brazil – as a study area. Within its extension, Minas Gerais has heterogeneity in soil classes and soil formation processes, phenomena triggered by such a divergent universe of environmental variables. Minas Gerais has no updated soil maps, making it a relevant study case for this research. Thus, we conclude that the Digital Soil Mapping process could be enriched by using different sources of Legacy Soil Data, even when there is no updated reference data.